10th International Scientific Conference of The Military Technical College 7 - 9 July, 2020. Issue 1 (November 2020) - Unknown
Abstract : Conference Program of The 19 th International Conference on Applied Mechanics and Mechanical Engineering, (AMME-19) Cairo 2020 List of Contents, Preface, Contributors, Conference Committees, Reviewers, Conference Program, Scientific Sessions are available in the pdf.